Grossgörschen 35 : Hat Geburtstag : 1964-1989. - Galerie Eva Poll, Berlin (Berlin : Galerie Eva Poll, 1989)
Albert, Hermann ; Baehr, Ulrich ; Berges, Werner ; Burggaller, Hans-Jürgen ; Diehl, Hans-Jürgen ; Donnan, Leiv Warren ; Dornhege, Hans-Georg ; Franoszek, Eduard ; Hödicke, Karl-Horst ; Knubel, Franz Rudolf ; Lange, Reinhard ; Lüpertz, Markus ; Petrick, Wolfgang ; Sorge, Peter ; Spengler, Arnulf ; Wintersberger, Lambert Maria
Grossgörschen 35 : Hat Geburtstag : 1964-1989, Galerie Eva Poll, Berlin, 16. Juni - 24. Juni 1989
boek